2013
DOI: 10.3762/bjnano.4.40
|View full text |Cite|
|
Sign up to set email alerts
|

Photocatalytic antibacterial performance of TiO2 and Ag-doped TiO2 against S. aureus. P. aeruginosa and E. coli

Abstract: SummaryThis paper reports the structural and optical properties and comparative photocatalytic activity of TiO2 and Ag-doped TiO2 nanoparticles against different bacterial strains under visible-light irradiation. The TiO2 and Ag-doped TiO2 photocatalysts were synthesized by acid catalyzed sol–gel technique and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), UV–vis spectroscopy and photoluminescence (PL). The XRD pattern revealed that the annealed sample of TiO2 has both anatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(136 citation statements)
references
References 19 publications
5
126
1
4
Order By: Relevance
“…These values were close to the present findings that the best inhibition zone for E. coli and S. aureus was 16.76 ± .10 and 18.45 ± 0.15 mm, respectively, with a significantly higher value attained using the melt-mixing method compared to the sol-gel process with the increased dispersion of Ag/TiO 2 gained with 3% Ag. Similarly, Gupta and colleagues [26] documented that an Ag/TiO 2 nanocomposite produced through the sol-gel process completely inactivated bacteria including E. coli and S. aureus when the TiO 2 NPs were doped with 3% Ag. In another study, the efficiency of Ag-TiO 2 NPs to completely kill E. coli populations was increased at an Ag concentration of 2.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were close to the present findings that the best inhibition zone for E. coli and S. aureus was 16.76 ± .10 and 18.45 ± 0.15 mm, respectively, with a significantly higher value attained using the melt-mixing method compared to the sol-gel process with the increased dispersion of Ag/TiO 2 gained with 3% Ag. Similarly, Gupta and colleagues [26] documented that an Ag/TiO 2 nanocomposite produced through the sol-gel process completely inactivated bacteria including E. coli and S. aureus when the TiO 2 NPs were doped with 3% Ag. In another study, the efficiency of Ag-TiO 2 NPs to completely kill E. coli populations was increased at an Ag concentration of 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of Ag + from the TiO 2 NPs may bestow antimicrobial properties. [5,8] Gupta et al [26] reported that Ag-TiO 2 nanocomposites having Figure 11. (a and b) LDPE produced using 0.5% Ag and 2.5% TiO 2 as well as 1% of silver, which were produced by the sol-gel method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the peaks at 2h = 32.5°are indicative of the brookite phase of the TiO 2 nanoparticles [20,21]. A strong rutile peak was observed for the 532-nm laser wavelength at 27.5° [22]. In addition, small peaks at 48°and 68.3°were observed at 532 nm which indicate the anatase phase [23,24], and the peaks at 56.25°and 70°represent the rutile phase [23,25] of the TiO 2 nanoparticles.…”
Section: Ag-tio 2 Compound Nanoparticlesmentioning
confidence: 99%
“…As a result, titanium(IV) hydroxide (Ti(OH) 4 Fig. 11 Relationship between the number of surviving E. coli bacteria as a function of the concentration of Ag-TiO 2 (US) (ultrasonic) and Ag nanoparticles generated by picosecond laser in deionised water with ultrasonic wave assisted.…”
Section: Generation Of Ag-tio 2 Cluster and Tio 2 Nanoparticlesmentioning
confidence: 99%
“…Both the hydrophilic and photocatalytic properties of TiO 2 nanoparticles are important for numerous applications, such as antimicrobial activity [4] and self-cleaning [5]. The photocatalytic activity of TiO 2 requires the activation with a UV light, which limits its applications.…”
Section: Introductionmentioning
confidence: 99%